Schistosoma “Eggs-Iting” the Host: Granuloma Formation and Egg Excretion - Schwartz, Christian; Fallon, Padraic G. (Frontiers in Immunology, 2018)
Schistosomiasis is major cause of morbidity in humans due to chronic infection with parasitic trematodes of the genus Schistosoma. Schistosomes have a complex life-cycle involving infections of a mammalian host, humans, and an aquatic snail intermediate host. In humans, adult male and female worms are within in the vasculature where eggs are laid that must be released from the host to continue the life cycle. S. mansoni and S. japonicum reside in the mesenteric circulation of the intestines with egg excreted in the faeces, whereas S. haematobium are present in the venus plexus of the bladder expelling eggs in the urine. In an amazing case of exploitation of the hosts immune system, this process of Schistosome eggs-iting the host is immune dependent. In this article, using S. mansoni as an example we explore how eggs laid in vasculature must usurp immunity to induce regulated inflammation to facilitate extravasation through the intestinal wall to be expelled in the faeces. We highlight the roles of immune cell populations, stromal factors, and egg secretions to provide a comprehensive overview over the current state of knowledge regarding a vastly unexplored mechanism.